Scattering of keV ions from a clean silicon single crystal surface. - Gauthier, Pierre. (University of Ottawa (Canada), 1992)
An apparatus for measuring energy and angular distributions of keV ions forward scattered from atomically clean silicon surfaces was designed and assembled. A consistent procedure for cleaning Si(100) single crystal surfaces under ultra-high vacuum was established. Experimentally, oxygen ions were surface scattered from a clean Si(100) sample and the ratios of outgoing negative to positive ions were measured. By using a positive oxygen beam and then a negative oxygen beam we obtained strong evidence that ions retain no memory of their initial charge state after it undergoes a violent collision with a single atom. The ratios of negative to positive scattered oxygen ions for both an incident O$\sp-$ ion beam and O$\sp+$ ion beam (under identical scattering conditions) were found to be the same (within statistical uncertainty) for incident energies between 6 keV and 20 keV.
Keywords: Physics, General.